2017
DOI: 10.1073/pnas.1615290114
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of a price incentive on free riding and electric energy consumption

Abstract: This article shows that a simple monetary incentive can dramatically reduce electric energy consumption (EEC) in the residential sector and simultaneously achieve a more desirable allocation of EEC costs. The analyses are based on data from a policy experiment conducted in 2011 and 2012 by a private housing company in about 1,800 apartments. Roughly 800 of the tenants (treatment group) were subject to a change from having unlimited EEC included in their rent to having to pay the market price for their own EEC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The intensive margin margin effect dominates among the largest firms. This heterogeneous response is consistent with a setting in which the bill savings from changing consumption do not cover the adjustment costs for small firms, and is in line with recent evidence from the residential sector (Elinder et al (2017)).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The intensive margin margin effect dominates among the largest firms. This heterogeneous response is consistent with a setting in which the bill savings from changing consumption do not cover the adjustment costs for small firms, and is in line with recent evidence from the residential sector (Elinder et al (2017)).…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, the savings occur at times when the value of electricity is likely to be high: during the hottest days of the year. Our finding that the largest customers are most responsive to contract type corroborates recent evidence from the residential sector in Sweden (Elinder et al (2017)). In contrast, contract type does not measurably impact consumption decisions for the smallest 90 percent of commercial customers.…”
Section: Introductionsupporting
confidence: 89%
“…6 We thus add to literature on misperceptions of price (Ito 2014;McRae and Meeks 2016), lack of information about the price (Jessoe and Rapson 2014;Kahn and Wolak 2013), and lack of salience (Allcott 2011;Allcott et al 2014) as factors that dampen the price elasticity of demand. The incentive mis-alignment within the household that we study resembles the incentive problem between landlords and tenants, which has been shown to lead to over-consumption of electricity (Levinson and Niemann 2004;Elinder et al 2017) and underinvestment in efficiency (Gillingham et al 2012;Myers 2015). 7 Intrahousehold inefficiencies might be especially important in poor countries, where gender roles are particularly imbalanced.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the increasing focus on occupant behaviour has shown that "behaviour change is fundamental to the success of energy efficiency schemes" because without proper use of technologies or knowledge of energy use by the people who use the technology, the full gains from the technology cannot be achieved (Fylan et al, 2016). Addressing this split incentive, especially in units that do not pay for their own utilities, can possibly save up to 25% in energy reductions (Elinder, Escobar, & Petré, 2017). It is worth noting, however, that the study's largest customers were the main cause of reductions of 25% from the above study and the same savings may not be realized if there is not a large heterogeneity in the size of customers.…”
Section: Split Incentivesmentioning
confidence: 99%
“…One study observed that when residents who previously had utilities included in their rent were required to pay for utilities, energy usage decreased by 25% (Elinder et al, 2017).…”
Section: Consider Revisiting Electricity Subsidy Arrangement For Socimentioning
confidence: 99%